Wilson-McAdoo families papers - McAdoo, Eleanor Wilson, 1889-1967.; Wilson, Margaret Woodrow, 1886-1944.
Correspondence, writings, speeches, statements, biographical materials, financial papers, clippings, photographs, and other papers relating to the McAdoo and Wilson families, chiefly Eleanor Wilson McAdoo and Margaret Woodrow Wilson. Includes material documenting Margaret's singing career, promotion of American schools as community centers, and experiences in Pondicherry, India, as a follower of the Hindu mystic, Aurobindo Ghose; and Eleanor's writings on the Wilson family. Other family members represented include Eleanor and Margaret's sisters, Jessie Woodrow Wilson Sayre and Ellen Axson Wilson, and Eleanor's husband, William Gibbs McAdoo. Subjects include national politics; McAdoo's service as U.S. secretary of the treasury and director general of railroads in the Woodrow Wilson administrations and his law practice in Los Angeles, Calif.; Jessie's husband, Francis Bowes Sayre, and their family; and Woodrow Wilson and his second wife, Edith Bolling Galt Wilson.
Wilson family including Margaret Woodrow Wilson and Eleanor Wilson McAdoo, daughters of President Woodrow Wilson.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ghose, Aurobindo, -- 1872-1950.; McAdoo, W. G. -- 1863-1941.; Sayre, Francis Bowes, -- 1885-1972.; Sayre, Jessie Woodrow Wilson, -- 1887-1933.; Wilson, Edith Bolling Galt, -- 1872-1961.; Wilson, Ellen Axson; Wilson, Woodrow, -- 1856-1924.; McAdoo family; Sayre family; Wilson family; United States. -- Department of the Treasury. -- Office of the Secretary; United States. -- Director General of the Railroads; Community centers; Mysticism -- Hinduism; Mysticism -- India; Practice of law -- California -- Los Angeles; Railroads and state -- United States; School facilities -- Extended use; Singing; Pondicherry (India) -- Religion; United States -- Economic policy -- 20th century; United States -- Politics and government -- 1901-1953.